INFLUENCE OF THERMAL TREATMENT ON CRYSTALLINITY, DEFECT STATE,STABILITY, AND PHOTONIC CHARACTERISTICS OF ZnO NANOPARTICLES - Mohsin, Mohammed; Abdulla, Muhamad (Science Journal of University of Zakho, 2026)
The sol-gel technique was successfully used to synthesize zinc oxide nanoparticles (ZnO NPs) from zinc acetate dehydrate as a reagent and sodium hydroxide as a medium to examine the influences of thermal treatment on the structural, morphological, and optical behaviour. Calcination was conducted at different temperatures ranging from 450°C to 750°C. The achieved zinc oxide nanoparticles were analyzed using various characterizations, including field emission scanning electron microscopy (FESEM), X-ray diffraction (XRD), UV-visible spectroscopy, and zeta potential analysis. The outcomes showed that calcination significantly affects crystallinity, particle size, bandgap, and stability. The ideal temperature emerged to be 550°C. X-ray diffraction validated the development of hexagonal wurtzite, demonstrating the highest crystallinity at 91.27%, the lowest crystallite size of 18.668 nm, the narrowest optical bandgap of 3.62 eV, and the best colloidal stability of -55.17 mV. These findings underscore the significance of heat control in tuning the properties of ZnO nanoparticles, rendering them appropriate for diverse applications in nanotechnology and optoelectronics.